Transformation of T-lymphoblastic lymphoma into acute myeloid leukemia after recurrence: a case report and literature review - Yang, Mengzhuo; Mei, Wenmiao; Zhao, Xiaoqiang (Frontiers in Oncology, 2025)
ObjectiveTo investigate the diagnosis and treatment of the condition of T-lymphoblastic lymphoma (T-LBL) transforming into acute myeloid leukemia (AML) following recurrence.MethodsWe conducted a retrospective analysis of a patient admitted to the First Affiliated Hospital of Henan University of Science and Technology in July 2022 with recurrent T-LBL that progressed to AML. Clinical manifestations, genetic and histopathological findings, and treatment outcomes were evaluated, complemented by a literature review.ResultsThe patient, initially diagnosed with T-LBL, achieved complete remission (CR) after combination chemotherapy. Following treatment cessation, the disease recurred and transformed into AML.ConclusionThe transformation of T-LBL into AML is exceedingly rare, and the underlying mechanisms of lineage switch remain unclear. Venetoclax combined with chemotherapy and allogeneic hematopoietic stem cell transplantation (allo-HSCT) may improve prognosis in such cases.